Colonic disease and the microbiota - F. Franceschi; M. De Siena; A. Gasbarrini (Microbiota in Health and Disease, 2020)
Microbiota is the set of microorganisms that compose our microbial community. The human microbiota comprises a vast collection of bacteria, viruses, fungi and protozoa that co-exist with us and establish physio-metabolic interactions with our cellular pathways. Qualitative and/or quantitative alterations of the microbiota, termed dysbiosis, has already been associated with a wide range of diseases and conditions, including inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), diverticular disease (DD), colorectal cancer (CRC), asthma, obesity, diabetes mellitus, hypertension, and cardiovascular disease. Microbiota changes in the intestinal lumen stimulate chronic inflammation possibly triggering disease in genetically predisposed individuals.